Transformasi Gereja Bagi Keadilan Ekonomi - Andar Gomos Pasaribu (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2023)
One of the most important dimensions of the economy is the creation of justice and common prosperity for all people in the world. The economy is both rules and norms forming a unified global society. Therefore, conversations and all systems that govern the economy must answer the most important question of the economy, namely whether the system formed and compiled by humans is able to bring social justice and shalom to all mankind. The biggest problem in addressing global poverty is the injustice of the economic system which makes the owners of capital richer, while the workers and the people are getting impoverished even though they have worked hard. This structured poverty has also resulted in a series of negative impacts of social life such as terrorism, environmental damage, racism and global discrimination. This article questions the role of the church in the phenomenon of economic injustice that has often been discussed in the global ecumenical community, for it seems the churches have not done much or even grasped the reality of this injustice. The true church is a church that is able to balance ecclesiocentricity and oikocentricity, meaning that the spiritual life of the church must be felt by members of the congregation socially and politically with social justice. Ecclesiology can only be understood if the church joins hands ecumenically, across religions and across nations in demanding an end to the injustice of the economic system while seeking equitable economic alternatives by absorbing the values of local wisdom.